Mitigation Strategy of Subsynchronous Oscillation Based on Fractional-Order Sliding Mode Control for VSC-MTDC Systems With DFIG-Based Wind Farm Access - Haiying Dong; Miaohong Su; Kaiqi Liu; Weiwei Zou (IEEE Access, 2020)
To solve the subsynchronous oscillation (SSO) caused by doubly-fed induction generator (DFIG)-based wind farm access in voltage source converter based multi-terminal direct current (VSC-MTDC) systems, the fractional-order sliding mode control (FOSMC) strategy is proposed to suppress the SSO and improve the system robustness. First, the rotor side converter (RSC) of the DFIG and the converter connected with the wind farm are linearized by the feedback linearization method. The stability of the internal system is ensured by the application of zero-dynamic theory. Then, the appropriate switching manifold surface and the exponential approach law vs are selected for the design of FOSMC strategy. The control law of the system can be derived when the stability of the system is ensured. After that, the designed FOSMC strategy is applied to the RSC and the VSC connected with the wind farm. To verify the superior performance of the proposed control strategy, the FOSMC strategy is compared with the traditional subsynchronous damping controller (SSDC) by time-domain simulation under different operating conditions. The simulation results show that the FOSMC strategy can effectively suppress the SSO under different operating conditions, stabilize the system quickly, and enhance the robustness of the system against parameter disturbances.